An Ayurvedic Approach for Treatment of Fissure in Ano: A Case Report of 32 Year Old Patient - Alok kumar Diwedi; Kiran Khandare; Rakesh Khatana; Harjodh Singh (Institute of Medico-legal Publications Pvt Ltd, 2021)
Anal Fissure is one of the major causes for pain at anal region. In this case report we are presenting case of32 year old male patient came to OPD of Shalya tantra with the chief complains of pain during defectionsince 20days, itching at perianal region since 15 days and bleeding per rectum since 13 days. InterventionIn this case report patient is treated by using Go ghrita for the management of acute fissure in ano. Goghrita was used for local application along with sitz bath.The effectiveness of Go ghrita was assessed bypain bleeding itching and healing. The patient has found effective relief from pain, bleeding, itching atperianal region using Go ghrita which has anti-inflammatory activity, antiulcer activity. The outcome of thismanagement is that Go ghrita is effective in the management of Fissure in ano . Patients who take all followup after treatment will have less chance of symptom reoccurrence.